2015
DOI: 10.14309/crj.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Pseudoaneursym as the Cause of Recurrent Gastrointestinal Bleeding in a Woman With Diffuse Scleroderma

Abstract: A 67-year-old woman with a 15-year history of intestinal scleroderma presented with recurrent melena. Upper endoscopies revealed a healing, non-bleeding, large gastric ulcer. After the third bleed, angiography demonstrated bleeding from a splenic artery pseudoaneurysm adjacent to the gastric ulcer. Scleroderma patients are at risk of bleeding from esophagitis or gastric arteriovenous malformations, while splenic artery pseudoaneurysms are primarily attributed to pancreatitis and trauma. This is the first repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…A literature search performed on the PubMed database revealed 11 reported cases of GI hemorrhage due to SAP rupture to date. 6,7,[9][10][11][12][13][14][15][16][17] In addition, because an SAP rupture is a life-threatening condition, a diagnosis should be promptly determined based on endoscopy or imaging modalities, especially CT. The fatal complications are independent of pseudoaneurysm size; therefore, treatment planning should occur immediately upon diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search performed on the PubMed database revealed 11 reported cases of GI hemorrhage due to SAP rupture to date. 6,7,[9][10][11][12][13][14][15][16][17] In addition, because an SAP rupture is a life-threatening condition, a diagnosis should be promptly determined based on endoscopy or imaging modalities, especially CT. The fatal complications are independent of pseudoaneurysm size; therefore, treatment planning should occur immediately upon diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] The most common causes of PASA include local inflammatory states (primarily chronic and acute pancreatitis) and trauma. 4,5,[11][12][13]17 Tessier et al 4 reported associations with pseudocysts in 41% of cases of pancreatic PASA. Among other less frequent causes, Hartman et al 17 described a PASA associated with scleroderma and gastric ulcer, with no history of pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,[11][12][13]17 Tessier et al 4 reported associations with pseudocysts in 41% of cases of pancreatic PASA. Among other less frequent causes, Hartman et al 17 described a PASA associated with scleroderma and gastric ulcer, with no history of pancreatitis. They assumed that the macrovascular disease of the scleroderma reduced the elasticity of vessels and caused microangiopathy of the vasa vasorum, leading to ischemia of the vascular wall, predisposing to pseudoaneurysm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Entre outras causas menos frequentes, descrevem um PSAE associado a esclerodermia e úlcera gástrica, sem história de pancreatite. Esses autores supõem que a doença macrovascular na esclerodermia cause diminuição da elasticidade dos vasos e microangiopatia da vasa vasorum, ocasionando isquemia da parede vascular, o que predispõe à formação de pseudoaneurisma (HARTMAN et al, 2015).…”
Section: Discussionunclassified